Multigene Panel Testing in Turkish Hereditary Cancer Syndrome Patients - Esra ARSLAN ATES; Ayberk TURKYILMAZ; Ceren ALAVANDA; Ozlem YILDIRIM; Ahmet Ilter GUNEY (Medeniyet Medical Journal)
Objective: Hereditary cancer syndromes (HCSs) are a heterogenous group of disorders caused by germline pathogenic variations in various genes that function in cell growth and proliferation. This study aimed to describe the germline variations in patients with hereditary cancer using multigene panels. Methods: The molecular and clinical findings of 218 patients with HCS were evaluated. In addition, 25 HCS-related genes were sequenced using a multigene panel, and variations were classified according to the American College of Medical Genetics and Genomics (ACMG) criteria. In total, 218 HCS patients predominantly with breast, colorectal, ovarian, gastric, and endometrium cancers were included. Results: Pathogenic variations in 12 distinct genes were detected in 36 of 218 (16.5%) cases. In this study, the most affected gene was the ATM gene, in which pathogenic variations were detected in 8 of 218 cases, followed by CHEK2 (3.2%), MUTYH (3.2%), BRIP1 (1.8%), BARD1 (0.9%), TP53 (0.9%), PALB2 (0.4%), MLH1 (0.4%), MSH2 (0.4%), PMS2 (0.4%), RAD50 (0.4%), and RAD51C (0.4%). Conclusions: This study contributes to genotype-phenotype correlation in HCSs and expands the variation spectrum by introducing three novel pathogenic variations. The wide spectrum of the gene pathogenic variations detected and the presence of multiple gene defects in the same patient make the multigene panel testing a valuable tool in detecting the hereditary forms of cancer and providing effective genetic counseling and family specific screening strategies.